Strategi Pemasaran Jasa Pendidikan dalam Meningkatkan Animo Masyarakat pada Masa Pandemi Covid-19 - Mahmud MY; Riftiyanti Savitri; Lesiana Oktorita (JMiE (Journal of Management in Education), 2021)
This research aims to find out the management of marketing of educational services in increasing public interest during the Covid-19 pandemic. This research uses descriptive qualitative research methods. Data is collected through observations, interviews, and documentation. The results of the study showed that the marketing of ma Al-Azhar Muaro Bungo education services during the Covid-19 pandemic was carried out by applying the concept of educational services marketing mix including marketing quality graduate products and karimah; price (tuition fee) is determined by the adjustment of the average economy of the student's parents; the place or location of the madrassa is in a strategic location; madrassa promotion is carried out directly and indirectly; Professional human resources and adequate facilities and infrastructure; The process of delivering educational services includes the delivery of facilities and facilities, learning activities, and extracurricular activities.